2021
DOI: 10.1002/dc.24695
|View full text |Cite
|
Sign up to set email alerts
|

Comparing scraping cytology with touch imprint cytology and frozen section analysis in the intraoperative diagnosis of sentinel lymph node metastasis in breast cancer

Abstract: Background Breast cancer is a common cancer in the female population. Sentinel lymph node (SLN) in breast cancer patients can be evaluated by different methods including intraoperative frozen section analysis (FSA), touch imprint cytology (TIC), and scraping cytology (SC). In this study, in addition to investigating TIC and FSA, we focused on SC to evaluate the diagnostic value of this almost new method. Materials and methods In this retrospective study, the quadrantectomy and sentinel lymph node resection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Additionally, the image quality scores, according to a junior pathologist, indicated that MEW‐M had superior image quality than TIC, with a median score of 3.1 vs 2.1 ( p < 0.0001). Furthermore, the lower cellular content and incomplete pathological structure in TIC made interpretation more challenging, such that a dedicated pathologist was required to resolve the issue 26 . From this perspective, promoting the use of MEW‐M in clinical settings could prove beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the image quality scores, according to a junior pathologist, indicated that MEW‐M had superior image quality than TIC, with a median score of 3.1 vs 2.1 ( p < 0.0001). Furthermore, the lower cellular content and incomplete pathological structure in TIC made interpretation more challenging, such that a dedicated pathologist was required to resolve the issue 26 . From this perspective, promoting the use of MEW‐M in clinical settings could prove beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lower cellular content and incomplete pathological structure in TIC made interpretation more challenging, such that a dedicated pathologist was required to resolve the issue. 26 From this perspective, promoting the use of MEW-M in clinical settings could prove beneficial.…”
Section: Mew-m Is a Novel Portable Imaging Microscopy Technique Thatmentioning
confidence: 99%
“…We assume that our MPM imaging method is promising, especially in intraoperative rapid diagnosis. Although it is critical to reduce the excision range in cancer surgery, 1 , 2 , 3 suboptimal accuracy is one of the most important concerns. This is partly attributed to sampling error caused by the limited observable area of the frozen section.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, histopathology plays an important role in the final diagnosis and intraoperative rapid diagnosis, which is critical for reducing the excision range in cancer surgery. 1 , 2 , 3 However, some problems are associated with typical histopathology‐based diagnostic procedures. Conventional methods can provide only planar two‐dimensional images; thus, it is not possible to observe three‐dimensional structures in diverse anatomical structures consisting of various cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation